1992
DOI: 10.1182/blood.v80.8.2052.bloodjournal8082052
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in patients with tumors producing colony-stimulating factor

Abstract: We investigated the cause of thrombocytosis in 14 patients with tumors producing colony-stimulating factor (CSF). Of the 14 patients, 10 had tumors producing granulocyte-CSF (G-CSF) and 4 had tumors producing granulocyte-macrophage--CSF (GM-CSF). Thrombocytosis of greater than 400 x 10(9)/L was noted in 8 of 10 patients with G-CSF-producing tumors and all 4 patients with GM-CSF-producing tumors. Median peak platelet counts were, respectively, 511 x 10(9)/L (range, 384 to 694 x 10(9)/L) and 579 x 10(9)/L (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…Platelet‐derived transforming growth factor‐β acts on cancer cells to activate the Smad and nuclear factor‐kappa β pathways, thus promoting cancer metastasis . Additionally, cancer cells can produce tumor‐related humoral factors and cytokines, such as granulocyte colony‐stimulating factor and interleukin‐6, which stimulate thrombopoiesis …”
Section: Discussionmentioning
confidence: 99%
“…Platelet‐derived transforming growth factor‐β acts on cancer cells to activate the Smad and nuclear factor‐kappa β pathways, thus promoting cancer metastasis . Additionally, cancer cells can produce tumor‐related humoral factors and cytokines, such as granulocyte colony‐stimulating factor and interleukin‐6, which stimulate thrombopoiesis …”
Section: Discussionmentioning
confidence: 99%
“…13 Indeed, Suzuki et al reported 25 years ago that primary tumor cells could produce and secrete G-CSF and GM-CSF leading to the stimulation of megakaryopoieses and thrombopoesis. 27 Focusing on ovarian cancer, Stone et al reported that plasma levels of TPO and IL-6 were significantly higher in patients with thrombocytosis than those without. In addition, the authors demonstrated, in a mouse model, an increased hepatic TPO synthesis in response to tumor-derived IL-6 and showed a correlation with paraneoplastic thrombocytosis.…”
Section: Activated Platelets and Thrombocytosismentioning
confidence: 99%
“…29,30 The elevation of TPO production promotes increased megakaryocyte growth differentiation and platelet production. [27][28][29][30][31] Tumor Cell-Induced Platelet Activation-Released Factors…”
Section: Activated Platelets and Thrombocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, en la mayoría de malignidades, el grado de trombocitosis en el paciente se encuentra inversamente correlacionado con su supervivencia, lo que le convierte en un marcador de mal pronóstico (Monreal et al, 1998;Symbas et al, 2000;Ikeda et al, 2002). Además, se conoce que los tumores pueden secretar citoquinas como IL-1, IL-6, GM-CSF y GCS-F, que estimulan la trombopoyesis y contribuyen al desarrollo de la trombocitosis (Suzuki et al, 1992;Estrov et al, 1995;Kaser et al, 2001).…”
Section: Desarrollo Tumoral Y Metástasisunclassified